Pemanfaatan Metode Importance Performance Analisis Untuk Mengukur Tingkat Kepuasan Penguna Website - Putra, Andriansah; Alamsyah, M. Nur; Susilo, Andrianto Tri (Journal of Information System Research (JOSH), 2024)
The existence of technology has provided many benefits for human life, one of which is in the field of education, both universities and schools. One of the information system websites that are widely used in Indonesian society, the website is an important aspect in providing various information from various sources that can be accessed by the world community. Visitors assess the performance of a site on its ease of use and attractiveness. To determine the quality of the website, it is necessary to take measurements, these measurements need to be carried out to determine the quality of a website so that we can understand the opinions of users on a website whether users are satisfied or the quality of the website still needs to be improved. The implementation of this research using the Importance Peformance Analysis (IPA) method combines the measurement of the importance level factor (Performance) and the performance level (Importance) in a two-dimensional graph that facilitates data explanation and gets practical suggestions. After measuring the results of this study, this website needs to improve its performance so that the performance level is higher than the level of expectation (Importance).